Inhibitory Effects of Habbat Al-Sauda Seed’s (Nigella Sativa) Extract Against Some Pathogenic Bacteria Isolated from Sulaimani Teaching Hospital - Hama, Salih (Iraqi Journal of Science, 2025)
To investigate the antibacterial effects of Nigella sativa seed extracts, three different concentrations of this extract (100 mg/ml , 0.1mg/ml , and 0.0 mg/ml –control-) were prepared in, and tested against (12) S. aureus isolates, (6) S. epidermidis, (15) P. aeruginosa and (14) E. coli isolates, which were isolated from Suleiman Teaching Hospital. For each bacterium three nutrient broth culture tubes were prepared and (0.25ml) of the pre-mentioned concentrations (tested) and distilled water (control) were added to the three cultivated tubes respectively. The inhibitory effects of seed extracts for the first and second cultivated tubes were determined turbidometrically at (640 nm). The effects were proportional with the extract concentration, the higher the concentration, the higher the inhibitory effects were. T-test was depended for statistically analyzing the obtained results from this study, significant differences were observed in regard to S. aureus (p= 0.00000474), S. epidermidis (p= 0.0327), P. aeruginosa (p= 0.00963) and E. coli (p= 0.03897) when the data from (100mg/ml) were compared with that of controls. Although the effects become limited (non-significant) when (0.1mg/ml) was used, but still within significant differences in regard to S. aureus (p= 0.000343) and E. coli (p= 0.0228).